The sterno-clavicular joint: anatomy, biomechanic, clinical features and aspects of manual therapy - G. Frosi; A. Sulli; M. Testa; M. Cutolo (PAGEPress Publications, 2004)
The sterno-clavicular joint covers one remarkable importance in the complex of the shoulder girdle. This review investigates the anatomy, biomechanics, main affections and involvement of this joint in the pathological processes of the shoulder girdle in its complex. Moreover, it focuses on the opportunities offered from the conservative treatment, using in particular the manual therapy. Active and passive, as well as against isometric resistance movements, are discussed. In particular, the passive mobilization is demonstrated effective in the restoration of joint mobility. The sterno- clavicular joint is not structured in order to complete great work loads and has the tendency to become hypermotile or unstable, if subordinate to overload works, becoming painful. In this case, the techniques of passive mobilization and of modulation of the pain turn out effective.